Implementation Of Drug Addict Rehabilitation Programs In Class IIa Cibinong Correctional Facility In 2023 - Safrian, Muhamad; Hartini, Sri; Purwaningsih, Prihatini (JURNAL MAHASISWA YUSTISI, 2025)
The increasing trend of drug-related crimes in Indonesia necessitates effective rehabilitation programs for drug addicts. Those convicted of drug abuse must undergo rehabilitation in designated institutions, including correctional facilities. This study aims to analyze the implementation mechanism and the challenges of the rehabilitation program for drug addicts in Class IIA Cibinong Correctional Facility in 2023. Using a normative empirical research method, this study incorporates field and library research with a statutory approach. Data were collected through literature review and field studies and analyzed using descriptive analysis. Findings indicate that the rehabilitation mechanism follows the Minister of Law and Human Rights Regulation No. 12 of 2017, comprising screening, assessment, and rehabilitation services. However, significant challenges exist, including facility limitations, funding constraints, time constraints, and human resource shortages. Addressing these challenges is crucial to ensuring effective rehabilitation and reintegration of drug addicts into society.